Interrelations between clinical-psychological features and bone mineral density changes in post-menopausal women undergoing anti-osteoporotic treatment: a two-year follow-up - Martino, Gabriella; Bellone, Federica; Vicario, Carmelo Mario; Gaudio, Agostino; Corica, Francesco; Squadrito, Giovanni; Lund-Jacobsen, Trine; Schwarz, Peter; Lo Coco, Gianluca; Morabito, Nunziata; Catalano, Antonino (Frontiers in Endocrinology, 2023)
Psychological features have been bidirectionally associated with osteoporosis, but it is still unclear whether patient’s anxiety fluctuations during the anti-osteoporotic treatment can have an impact on bone mineral density (BMD) variation. The aim of this study was to investigate the interrelations between psychological distress features, such as anxiety, depression, health-related QoL (HRQoL) and bone health in women receiving anti-osteoporotic treatment. 192 post-menopausal osteoporotic women were treated with alendronate or risedronate according to the standard procedure The levels of anxiety, depression, and perceived HRQoL, along with BMD, were assessed at baseline and at a 2-year follow-up. At the end of the study, the patients showed a statistically significant increase of both psychic and somatic anxiety (p<0.0001) and exhibited a worsening of depressive symptoms (p<0.0001), whereas HRQoL showed no change. BMD improved and no incident fractures occurred. BMD variation (ΔBMD) at lumbar spine was significantly associated with anxiety levels (r=0.23, p=0.021). Multiple regression analysis showed that both patients’ worsening anxiety levels (β = -0.1283, SE=0.06142, p=0.04) and their treatment adherence (β=0.09, SE=0.02, p=0.0006) were independently associated with ΔBMD. The findings of the current follow-up study suggest that BMD in post-menopausal women undergoing anti-osteoporotic treatment was predicted by treatment adherence and anxiety change over time.